A REVIEW ON SKIN WHITENING PROPERTY OF PLANT EXTRACTS - JENNIFER, C.; STEPHIE, C.M.; ABHISHRI, S.B.; SHALINI B. U (International Journal of Pharma and Bio Sciences, 2012)
One of the serious aesthetic problems in human beings is skin darkening which is more prevalent in middle aged and elderly individuals. Skin whitening is the practice of using chemical substances or traditional herbal formulations, in an attempt to lighten skin tone or provide an even skin complexion by the reduction of concentration of the pigment melanin. Tyrosinase is the key enzyme in melanin synthesis. Tyrosine inhibitors are the substances which reduce or block melanin synthesis leading to skin whitening. A number of potent tyrosinase inhibitors are from synthetic, semi-synthetic and natural origins. Natural cosmetics is a growing industry manufacturing skin whitening products which replaces harsh chemicals with natural plant extracts. The diverse medicinal plants extract with potent skin whitening property are discussed.